Gut Leakage of Fungal‐Related Products: Turning Up the Heat for HIV Infection - Isnard, Stéphane; Lin, John; Bu, Simeng; Fombuena, Brandon; Royston, Léna; Routy, Jean-Pierre (Frontiers in Immunology, 2021)
The intestinal epithelial layer serves as a physical and functional barrier between the microbiota in the lumen and immunologically active submucosa. Th17 T-cell function protects the gut epithelium from aggression from microbes and their by-products. Loss of barrier function has been associated with enhanced translocation of microbial products which act as endotoxins, leading to local and systemic immune activation. Whereas the inflammatory role of LPS produced by Gram-negative bacteria has been extensively studied, the role of fungal products such as β-D-glucan remains only partially understood. As HIV infection is characterized by impaired gut Th17 function and increased gut permeability, we critically review mechanisms of immune activation related to fungal translocation in this viral infection. Additionally, we discuss markers of fungal translocation for diagnosis and monitoring of experimental treatment responses. Targeting gut barrier dysfunction and reducing fungal translocation are emerging strategies for the prevention and treatment of HIV-associated inflammation and may prove useful in other inflammatory chronic diseases.